Protease purification from Bacillus amyloliquefaciens B7 using aqueous two phase system - Abd Samad , Nadiah Syuhada; Amid, Azura; Jimat, Dzun Noraini; Ab. Shukor, Nurul Aqilah (Kulliyah of Engineering, International Islamic University Malaysia, 2016)

(untitled)
Bacillus amyloliquefaciens B7 was isolated from fish fermented sauce and identified as protease producer. Generally, in downstream processing, purification of enzyme consumes high cost in terms of reagents and equipment used. Moreover, harsh purification methods used might cause denaturation of enzymes. Therefore, there is a high demand for efficient and low-cost extraction and purification methods. Aqueous two-phase system (ATPS) is an alternative that should be considered as it is simple, rapid separation yet cause little denaturation. Protease produced by B. amyloliquefaciens B7 was partitioned in two different ATPS, which are PEG/potassium phosphate and PEG/sodium citrate, and best separation was found in PEG/sodium citrate based on protease specific activity. Protease activity was determined using casein as the substrate. Using response surface methodology design, two independent variables which are pH and temperature were varied during protease purification by aqueous two-phase system composed of PEG 1500/sodium citrate and the highest enzyme activity was found at the interface phase. Optimum purification method observed is at pH 6, 30OC, 27 % (w/w) of PEG and 34 % (w/w) of Sodium Citrate and the highest enzyme activity achieved is 0.19± 0.010 U/ml.